Phytochemicals and bioactivities of cinnamomum porrectum (Roxb.) kosterm and cinnamomum mollissimum hook F - Fatin Fasihah Masnon, 1990- author; Farediah Ahmad, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2014